Scaffolding multilingualism in kindergarten children: A case study (Scholars' Journal, 2020)
This qualitative case study research entitled ‘Scaffolding multilingualism in kindergarten children: A case study’ explored how kindergarten children face learning and communication barriers when they have different home language which is not the language of instruction at school and language of others at school. In addition, it revealed how kindergarten children's language identity and cognitive investment are not allowed by the monolingually biased pedagogical approach. It has presented the scenario of scaffolding monolingual children to multilingual basing their home language as the founding scaffold ingredients. A newly admitted kindergarten girl in pre-kindergarten school was the main source of the case study including her mother and her teacher for supporting information. Interviews and notes of observation and informal communication were the research tools used for data collection. Multilingual development of the home monolingual child is the thematic issue of this study.